The matrix as a transitory form: The evolution of FMC technologies 2001-2016 - Nicolay Worren (Journal of Organization Design, 2017)
Introduction: The matrix structure is sometimes presented as an inevitable "end point" for organizations that must adapt to an increasingly complex business environment. However, observations of the structure of firms do not always confirm this view. Case description :The paper describes the evolution of FMC Subsea, a large division of the global technology firm FMC Technologies (now TechnipFMC). Discussion and evaluation: During the 2001-2016 time period, the firm's organizational structure underwent three significant changes. The firm was originally organized by geography. In 2011, it introduced global product units, which resulted in dual reporting lines (i.e., a matrix structure) for some regional managers. However, in 2015, it separated the product lines from the regional units, thereby eliminating the need for dual reporting. Conclusion: This example suggests that the matrix structure may sometimes be a transitory form that eventually gives way to a simpler-yet still multidimensional-structure.
Keywords: 650; Multinational firms; Matrix structures; Multidimensional organizational models; Complexity; Simplification